2019
DOI: 10.1149/2.1011914jes
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Borosilicate Glass Separators as an Electrolyte Additive Donor for Improving the Electrochemical Performance of Lithium-Ion Batteries

Abstract: In order to replace today's used electrochemical passive polymer-based lithium-ion battery separators, custom-made ultrathin micrometer-sized glass platelets are being tested as separators. Ions are leached from the glass by hydrofluoric acid (HF), which is typically present in LiPF 6 containing electrolytes. The ions act as an electrolyte additive and show an effect on electrochemical cell parameters with progressing battery cycling. For comparability, different glass compositions are investigated and are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…8a. 98 They found that the sodium borosilicate glass membrane exhibits acceptable cycle stability in LFP‖Li cells (Fig. 8b).…”
Section: Acid-scavenging By Functionalized Separatorsmentioning
confidence: 95%
See 3 more Smart Citations
“…8a. 98 They found that the sodium borosilicate glass membrane exhibits acceptable cycle stability in LFP‖Li cells (Fig. 8b).…”
Section: Acid-scavenging By Functionalized Separatorsmentioning
confidence: 95%
“…Reproduced with permission. 98 Copyright 2019, IOP Publishing. (b) Cycling performance of LFP8Gr cells with commercial Celgard 2325 and different glass separator at 1C.…”
Section: H 2 O Scavenging Separatorsmentioning
confidence: 99%
See 2 more Smart Citations